IMPLEMENTASI DATA PANEL SPASIAL TERHADAP TINGKAT PRODUK DOMESTIK REGIONAL BRUTO DI PROVINSI BALI - ASTUTI, NI MADE ARY DHARMA WIDYA; SUSILAWATI, MADE; SUCIPTAWATI, NI LUH PUTU (E-Jurnal Matematika; Vol 10 No 2 (2021), 2021)
Gross Regional Domestic Product (G RD P) is an economic indicator to see the economic movements of a region during a certain period, whether based on current and constant price. Economic activities in a region use the G RD P calculation based on current prices by industrial base year 2010 . In 2019, Bali's economic growth increased by , exceeding national economic growth of . Using spatial panel data in analysis consists of common effect model, fixed individual effect model, fixed time effect model, random effect model, and spatial lag fixed effect model. The best model to modeling G RD P Bali Province is spatial lag fixed effect which has a difference in constant values ?? at any time, with  of 99.41 percent , the remaining is explained by other variables not examined